Sulfonimidamide as a directing agent for Pd-catalyzed regioselective oxidative C–H acyloxylation of arenes. Issue 43 (25th October 2019) - Irfana Jesin, C.P.; Ravindra, S.; Nandi, Ganesh Chandra
Abstract: In this report, we describe the utilization of sulfonimidamide (SIA) as a novel directing group for a Pd-catalyzed regioselective oxidative C–H acyloxylation of aryl group of N -aroyl part of SIA in moderate to good yields in the presence of (Diacetoxyiodo)benzene (PhI(OAc)2 ) as an oxidizing agent and alkanoic acid as solvent. The solvent alkanoic acid is found to be the source of acyloxylation. Graphical abstract: Image 1 Highlights: Sulfonimidamide has been used as a directing agent for Pd-catalyzed regioselective oxidative C–H acyloxylation of arenes. The solvent (Carboxylic acid) is acting as a source for acyloxylation. The method is regioselective.